Funeral of Kropotkin. A group of released anarchist prisoners arrives at the Palace of Labour in Moscow. In the crowd: Gujewski(?), Mratschni(?), Olonetski(?), Taratuta(?), Aron Baron and David Kogan. Place of persons indicated on the back
Funeral of Kropotkin. A group of released anarchist prisoners arrives at the Palace of Labour in Moscow. In the crowd: Gujewski(?), Mratschni(?), Olonetski(?), Taratuta(?), Aron Baron and David Kogan. Place of persons indicated on the back.